2000
DOI: 10.1677/joe.0.1640171
|View full text |Cite
|
Sign up to set email alerts
|

8-bromo-cyclicAMP stimulates glucose transporter-1 expression in a human choriocarcinoma cell line

Abstract: Facilitative glucose transporter-1 (GLUT1) is abundant in trophoblast cells and is responsible for glucose transport in the placenta. However, the change in GLUT expression in human placenta upon trophoblast differentiation remains to be clarified. Therefore, we first examined the localization of GLUT1 and GLUT3 using human firsttrimester chorionic villi. We found that GLUT1 and GLUT3 were mainly localized to syncytiotrophoblast and cytotrophoblast cells respectively. We analyzed whether placental GLUT1 and GL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 38 publications
(29 reference statements)
2
27
0
Order By: Relevance
“…cAMP treatment resulted in increased secretion of ␤-HCG into the media indicating differentiation of the BeWo cells as previously reported by others (24) and therefore served as a positive control for viability. PGH secretion was also increased by cAMP (p ϭ 0.003) (Fig.…”
Section: Resultssupporting
confidence: 66%
“…cAMP treatment resulted in increased secretion of ␤-HCG into the media indicating differentiation of the BeWo cells as previously reported by others (24) and therefore served as a positive control for viability. PGH secretion was also increased by cAMP (p ϭ 0.003) (Fig.…”
Section: Resultssupporting
confidence: 66%
“…We found that a mixed population of cells did not transcytose virus as effectively as a monolayer of undifferentiated cells. This may be due to changes in BeWo cellular protein expression accompanying maturation that reduced virus attachment and transport (33,35,39,43). As transport of molecules across the maternal-fetal barrier must continue to take place throughout pregnancy, it is likely that specific cell factors play a role in HBV transport and that these change with cellular differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous pathways linking changes in cAMP to effects on glucose metabolism. For example chronic treatment with cAMP analogues increased glucose utilization by up-regulating GLUT-1 expression in human choriocarcinoma cells (68), although opposite results were observed in primary mouse placental cells (69). In insulin-sensitive tissues, several studies have shown that glucose uptake was enhanced by regulation of GLUT-1 expression through the cAMP/protein kinase A pathway.…”
Section: Fig 6 Effect Of Pio On Glut-1 Expressionmentioning
confidence: 99%